PYOPNEUMOTHORAX CAUSED BY PREVOTELLA INTERMEDIATA: AN INTERESTING CASE REPORT - Samad, Abdul; Naz, Farah; Butt, Nauman Ismat; Sarwar, Sajjad; Ghoauri, Muhammad Sohail Ajmal; Zahid, Ayesha (Journal of Ayub Medical College Abbottabad, 2024)
Prevotella species are usually seen in the intestinal tract including oral cavity as commensal bacteria and can lead to periodontal infections in immunocompetent patients. However, in patients who are immunocompromised, Prevotella can cause infections at other sites. A 35-year-old gentleman presented with 1-month history of high-grade fever and right sided pleuritic chest pain. On examination, he was in discomfort due to pain, with temperature 103 oF, pulse 104 beats per minute, blood pressure 130/90 mmHg, respiratory rate 22 breaths per minute and O2 saturation 94% on room air. Oral cavity revealed poor hygiene with left lower carious incisor. There was reduced chest expansion in right sub-scapular region with reduced vocal fremitus, dull percussion note, absent breath sounds and reduced vocal resonance. WBC count was raised at 43,600 per cm. X-ray followed by HRCT chest demonstrated peripheral opacifications with air-fluid level in right lower zone due to loculated pyopneumothorax and pleural thickening. Ultrasound guided chest tube thoracostomy in the loculated pyoneumothorax aspirated 1200 ml of foul-smelling reddish-tinged pus which revealed growth of anaerobic gram-negative rods of Prevotella Intermediata on culture, which was sensitive to amoxicillin-clavulanate and metronidazole. Work up of immunosuppressive causes was negative. The patient responded well to treatment and was asymptomatic at follow-up after 6 weeks.